Consumer Goods Classification - Revisited - Rekettye, Gábor (The Hungarian Journal of Marketing and Management, 2019)
The paper is arguing with the statements of the paper written by Törőcsik and Jakopánecz about the idea to modify the international marketing classification of the consumer products (published in 2010 in the second issue of this Journal). They suggested in their article that the products which evoke massive customer resistance from the part of the consumers (like the vaccine against H1N1 in 2010 in Hungary) should constitute a new subgroup of the consumer goods beside of the convenience, shopping and specialty goods triad. Present paper lists a line of contra arguments and comes to the conclusion that the this suggestion is scientifically not acceptable and goes even so far as to question the presence of the unsought goods category as presented in some marketing handbooks.